The Effect of Brand Experience on Brand Engagement and Brand Equity Mediated by Brand Love Apple Users - Syamsuddin, Siti Fatimah; Fadhilla, Hanifa Nur (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2024)
The influence of brand experience on brand engagement and brand equity among Apple customers in Yogyakarta was examined in this study. In addition, the purpose of this study is to gain an understanding of how brand experience can influence brand engagement and value in a competitive market. This research uses a quantitative approach with Partial Least Square (PLS) version 4.0 analysis technique. The research sample consists of 150 people who are in Yogyakarta and use Apple products. To collect data, a questionnaire was used to measure the variables under study. The results of the analysis show that brand experience has a positive and significant effect on brand love, brand involvement, and brand wealth. In addition, there is evidence that brand love significantly regulates brand experience with two other factors, namely brand engagement and brand equity. A good brand experience can increase emotional attachment and customer value, according to the findings of this study. The study concludes that a good brand experience is critical to building customer engagement and value with the brand. To increase customer loyalty and strengthen the brand's position in the market, marketers should concentrate on creating pleasant experiences. These results are highly beneficial for a company's marketing strategy, especially for premium brands like Apple.